CHES, MCHES, and/or CPH? Selecting the Best Credential for You. Issue 2 (March 2019) - Kerr, Dianne; Blavos, Alexis; Hancher-Rauch, Heidi; Brookins-Fisher, Jodi; Thompson, Amy
The health education profession within the broader context of public health has chosen certification to grant recognition to individuals meeting certain standards, as well as optional accreditation of academic programs. Regarding certification options for health education professionals, those who qualify may sit for the exams to achieve one of the following certifications: Certified Health Education Specialist (CHES), Master Certified Health Education Specialist (MCHES), or Certified in Public Health (CPH). Some health education and other professionals may be familiar with the concept of certification but may not be aware of the value of certification for the profession, their options for certification, or the processes of certification. This article provides information on CHES, MCHES, and CPH certifications and compares and contrasts their requirements. While many professionals may choose one credential over another, others may decide to pursue CHES/MCHES and the CPH. Credentialing continues to be an important part of advancing the health education profession and ensuring that those practicing in the field are highly qualified.